1993
DOI: 10.1016/0014-5793(93)80561-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c‐jun/AP‐1 during myogenic differentiation in mouse C2C12 myoblasts

Abstract: Mitogen withdrawal triggers myogenic differentiation in skeletal myoblasts in culture. We have examined the expression of the proto‐oncogene c‐jun during this process in mouse C2C12 myoblasts. c‐jun belongs to a family of immediate early genes whose expression is activated in cultured cells in response to the addition of serum growth factors. Interestingly, expression of c‐jun was maintained in mouse C2C12 and rat L6 myoblasts undergoing myogenic differentiation under low‐serum conditions. Previously it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In relation to AP-1 activation, TNF-a has been shown to increase c-jun expression in C2C12 cells [27]. Interestingly, overexpression of c-jun mimics the observed effect of TNF-a upon differentiation; indeed, it results in decreased myoblast differentiation [28]. Tumour mediators, proteolysis-inducing factor in particular, also seem to be able to increase NF-kB expression in cultured muscle cells, this possibly being linked with increased proteolysis [29].…”
Section: Muscle Wastingmentioning
confidence: 91%
“…In relation to AP-1 activation, TNF-a has been shown to increase c-jun expression in C2C12 cells [27]. Interestingly, overexpression of c-jun mimics the observed effect of TNF-a upon differentiation; indeed, it results in decreased myoblast differentiation [28]. Tumour mediators, proteolysis-inducing factor in particular, also seem to be able to increase NF-kB expression in cultured muscle cells, this possibly being linked with increased proteolysis [29].…”
Section: Muscle Wastingmentioning
confidence: 91%
“…Following activation, JNK phosphorylates several transcription factors including activating transcription factor-2 (17), Elk-1 (18), Sap-1a (19), and c-Jun (20) which are involved in regulating numerous genes implicated in cell proliferation, transformation, differentiation, and DNA repair (21)(22)(23)(24). Recent studies also show that oxidative stress can activate HSF and increase HSP70 gene expression (25).…”
mentioning
confidence: 99%
“…It has been suggested that in muscle cells, AP1 and MyoD functionally antagonize each other through physical association between Jun and MyoD [12], so that upon muscle differentiation MyoD might block AP1‐dependent activation of the vimentin promoter. However, no decrease in c‐jun expression or AP1 binding activity was observed in C2C12 cells [13]. NF‐κB was reported to stimulate cell proliferation and to block muscle differentiation through activation of the cyclin D1 gene [14], suggesting that the positive effect of NF‐κB on the vimentin promoter may be counteracted during myogenesis.…”
Section: Discussionmentioning
confidence: 93%